Improving Energy Efficiency by Utilizing Wetted Cellulose Pads in Passive Cooling Systems - Ebrahim Morady; Madjid Soltani; Farshad Moradi Kashkooli; Masoud Ziabasharhagh; Armughan Al-Haq; Jatin Nathwani (Energies, 2022)
The effectiveness of using wetted cellulose pads on improving the performance of two conventional passive cooling systems has been evaluated. First, an experimental design was developed to determine the impact of using a wetted cellulose pad on the temperature and velocity of the airflow. A cellulose pad (7090 model) with a cross-sectional area of 0.5 × 0.5 m2 and three different thicknesses of 10, 15, and 30 cm were selected and tested. The results indicated that using wetted cellulose pads with thicknesses ranging from 10–30 cm decreased the outlet airflow temperature from 11.3 to 13.7 °C on average. For free airflow at velocity 3.5 m/s, the outlet airflow velocity from the wetted cellulose pad decreased to 0.9, 0.7 and 0.6 m/s, respectively, for cellulose pads with thicknesses of 10, 15, and 30 cm. By applying experimental results on a psychrometric chart, the humidity ratio of outlet airflow was obtained between 40–70%. The study established airflow velocity as the critical parameter in passive cooling systems. With the novel concept of combining wetted cellulose pads for passive cooling systems (i.e., wind catchers and induced ventilation), there is good potential to reduce the energy requirements for thermal comfort in buildings in regions with a hot and arid climate.